2016
DOI: 10.1080/14397595.2016.1189139
|View full text |Cite
|
Sign up to set email alerts
|

A case report of cutaneous polyarteritis nodosa in siblings

Abstract: Cutaneous polyarteritis nodosa (CPAN) is characterized by a necrotizing vasculitis of small and medium-sized arteries in the skin, which can be associated with fever, arthralgia, myalgia, and neuropathy, but, unlike polyarteritis nodosa (PAN), there is no visceral involvement. CPAN is rare in childhood. We report two siblings who developed CPAN during childhood. Interestingly, both had Mediterranean fever gene (MEFV) mutation, i.e. heterozygous E148Q. They also shared HLA-A24, -DR15 alleles. Simultaneous occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The case presented here exemplifies the possible difficulties in diagnosing vasculitis due to inconclusive clinical manifestations, which is especially true for rare disease entities, such as PAN in children [7, 21, 22]. In the case of our patient, the symptoms and laboratory test results were indicative of several disease entities.…”
Section: Discussionmentioning
confidence: 53%
“…The case presented here exemplifies the possible difficulties in diagnosing vasculitis due to inconclusive clinical manifestations, which is especially true for rare disease entities, such as PAN in children [7, 21, 22]. In the case of our patient, the symptoms and laboratory test results were indicative of several disease entities.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have found FDG-PET sensitive for detecting disseminated spots throughout subcutaneous tissue and muscle associated with cutaneous polyarteritis nodosa (CPAN), a rare manifestation sometimes referred to as leopard skin appearance (56). CPAN is characterized by necrotizing vasculitis of medium and small arteries of the skin and is also associated with extra-cutaneous findings such as fever, malaise, and neuropathy but no visceral involvement (57).…”
Section: Polyarteritis Nodosa (Pan)mentioning
confidence: 99%